PENGARUH LINGKUNGAN SEKOLAH DAN POLA ASUH ORANG TUA TERHADAP PEMBENTUKAN KARAKTER ANAK USIA 5 – 6 TAHUN: (TK Swasta dan TK Negeri) - Budi Hermaini; Neneng Alawiyah; Dewi Sekarsari; Dian Novita; Mutiara Magta (Institut Madani Nusantara, 2023)
This research is motivated by the importance of disciplining children from an early age as a foundation in forming an orderly and responsible society. The consistency of schools and parents in applying discipline to children greatly influences the child's personality in the future. The purpose of this study was to determine the influence of the school environment and parenting in applying discipline to children at home. This study used a cross-sectional study design which was conducted in four schools in South Tangerang City, Pamulang District and Central Jakarta. The selection of schools was carried out purposively (purposively) based on several considerations, namely (1) schools with more than 100 students each year; (2) public kindergarten and state kindergarten. Furthermore, the sample criteria in this study were kindergarten B class children from selected schools aged 5 to 6 years, two private kindergarten schools and two public kindergarten schools from each school, 30 children were selected, so the total number of samples was 120 children. The type of data used in this research is primary and secondary data. Data analysis used in this research is descriptive statistical analysis and inferential statistical analysis. The inferential statistical analysis used was the Spearman and Pearson correlation test, as well as the t-test of differences. The results of the study show that there is a significant relationship between parenting styles and the level of discipline of children. Parents who are actively involved in parenting have an impact on activities at school in terms of forming child discipline. Teachers and parents always synergize well in improving child discipline. So that the expectations and goals to be achieved are fulfilled as expected.